2021
DOI: 10.20944/preprints202106.0555.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biogenic Silver Nanoparticles from Iris Tuberosa as Potential Preservative In Cosmetic Products

Abstract: Biogenic-Silver nanoparticles emerge as new nanosilver platfmorm that allow to obtain silver nanoparticles via “green chemistry”. In our study we obtained biogenic-Silver nanoparticles from Iris tuberosa leaves extract. Nanoparticles were characterized by UV-vis spectroscopy, dinnamical light scattering technique and Transmission electron microscope, showing spheric and irregular nanoparticles with 5 to 50 nm in diameter. Antioxidant and antimicrobial properties were evaluated against typic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Al-Dhabi et al [59] studied AgNPs from marine-derived actinomycetes that exhibited significantly higher antibacterial activity against gram-negative bacteria, namely E. coli (31.25 μg/ml), K. pneumoniae (62.5 μg/ml) and P. aeruginosa (15.6 μg/ml) than gram-positive bacteria like Enterococcus faecalis (125 μg/ml), Bacillus subtilis (250 μg/ml) and Staphylococcus epidermidis (250 μg/ml), which supports the tendency found in our studies. In contrast, Mondéjar-López et al [60] reported that the MICs of biogenic AgNPs from Iris tuberosa against P. aeruginosa and S. aureus (14.1 μg/ml) were much lower than those against E. coli (44.4 μg ml -1 ). Meanwhile, Rautela et al [61] reported that the MICs of bio-AgNPs from Tectona grandis seed extract against Bacillus cereus, S. aureus, and E. coli were found to be 5.2, 2.6, and 2.0μg/ml, respectively.…”
Section: Assessment Of Agnp Antimicrobial Activity Determination Of M...mentioning
confidence: 89%
“…Al-Dhabi et al [59] studied AgNPs from marine-derived actinomycetes that exhibited significantly higher antibacterial activity against gram-negative bacteria, namely E. coli (31.25 μg/ml), K. pneumoniae (62.5 μg/ml) and P. aeruginosa (15.6 μg/ml) than gram-positive bacteria like Enterococcus faecalis (125 μg/ml), Bacillus subtilis (250 μg/ml) and Staphylococcus epidermidis (250 μg/ml), which supports the tendency found in our studies. In contrast, Mondéjar-López et al [60] reported that the MICs of biogenic AgNPs from Iris tuberosa against P. aeruginosa and S. aureus (14.1 μg/ml) were much lower than those against E. coli (44.4 μg ml -1 ). Meanwhile, Rautela et al [61] reported that the MICs of bio-AgNPs from Tectona grandis seed extract against Bacillus cereus, S. aureus, and E. coli were found to be 5.2, 2.6, and 2.0μg/ml, respectively.…”
Section: Assessment Of Agnp Antimicrobial Activity Determination Of M...mentioning
confidence: 89%